Impact of Kadarzi Program on Stunting Reduction: Dampak Program Kadarzi terhadap Penanggulangan Stunting - Rahayu, Linda; Riyadh, Ahmad (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to assess the effectiveness of the nutrition-aware family program (kadarzi) in addressing stunting in Payan Hamlet, Pabean Village, Sedati District, Sidoarjo Regency, Indonesia. The research utilized a descriptive qualitative approach, incorporating observation, interviews, and both primary and secondary data. The authors employed purposive sampling and the data analysis model of Miles and Huberman, focusing on data reduction, presentation, and drawing conclusions. The study's goal was to evaluate the program's impact based on the effectiveness theory proposed by Sutrisno (2017), which includes five indicators: target accuracy, program understanding, timeliness, goal achievement, and real change. The results indicate that while the program demonstrated success in some areas, improvements are needed in terms of program understanding. The implications of this study provide valuable insights for the ongoing global efforts to combat stunting and improve child nutrition. Highlight : The study utilized a descriptive qualitative approach, incorporating observation, interviews, and both primary and secondary data. The research employed purposive sampling and the data analysis model of Miles and Huberman, focusing on data reduction, presentation, and drawing conclusions. The study aimed to evaluate the program's impact based on the effectiveness theory proposed by Sutrisno (2017), which includes five indicators: target accuracy, program understanding, timeliness, goal achievement, and real change. Keywords: Kadarzi program, stunting, nutrition, Sidoarjo, Indonesia